Unleashing the green potential: incorporating eco-business and key tourism elements in Kandri Semarang's Villages - Aditya Wisnu Wardana; Eko Nursanty; Mai Lê Ngọc Hà; Astari Wulandari (Institute for Advanced Science Social, and Sustainable Future, 2023)
This paper explores the potential of incorporating eco-business and key tourism elements in Kandri Semarang's villages to enhance their competitive advantage in suburban areas. A case study approach was adopted to examine the status of tourism villages in Kandri Semarang and identify the key tourism elements that can be integrated with eco-business practices. The findings suggest that by embracing sustainable practices and capitalizing on the area's unique natural and cultural resources, tourism villages in Kandri Semarang can differentiate themselves from competitors and attract more tourists. The paper concludes by providing practical recommendations for stakeholders to collaborate and create a sustainable tourism ecosystem that benefits the local community and the environment.